The Role Of Information And Communication Technology In Enhancing Network Security In The Cyber Era - Wahyuni, Ritna (Riset Sinergi Indonesia (RISINDO), 2024)
In the era of rapid digitalization, network security has become a critical concern for organizations and individuals alike. The role of Information and Communication Technology (ICT) in enhancing network security is pivotal in safeguarding sensitive data and maintaining the integrity of digital infrastructures. This paper explores the various ways ICT tools and strategies can be applied to strengthen network security measures, particularly in the context of emerging cyber threats. By leveraging advanced technologies such as firewalls, encryption, intrusion detection systems, and artificial intelligence, organizations can better prevent, detect, and respond to potential security breaches. Additionally, the integration of ICT in cybersecurity practices supports real-time monitoring, threat analysis, and proactive risk management. The findings highlight the importance of adopting a comprehensive and adaptive approach to network security, emphasizing the need for continuous updates and innovations to address the evolving landscape of cyber threats. Overall, ICT plays a crucial role in creating resilient network security frameworks that ensure the protection of data and digital assets in an increasingly connected world.